2022
DOI: 10.3390/nu14224934
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D and Calcium as Key Potential Factors Related to Colorectal Cancer Prevention and Treatment: A Systematic Review

Abstract: Colorectal cancer (CRC) is currently considered one of the most common and lethal types of tumors. Nutrition is of notorious relevance, given its influence in CRC prevention and treatment. This systematic review aimed to revise and update the state of knowledge regarding the potential role of vitamin D and calcium as key factors involved in the prevention and treatment of CRC. A literature search was performed in PubMed and Web of Science. A total of eight studies were finally included in the present review. V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Additionally, clinical trials have found that vitamin D supplementation can improve the survival rates of cancer patients 28 . Vitamin D supplementation, as indicated by a systematic review and meta-analysis, was associated with a 30% reduction in overall adverse survival outcomes, a 24% reduction in CRC-speci c death, and a 33% reduction in disease progression or survival 29 .…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, clinical trials have found that vitamin D supplementation can improve the survival rates of cancer patients 28 . Vitamin D supplementation, as indicated by a systematic review and meta-analysis, was associated with a 30% reduction in overall adverse survival outcomes, a 24% reduction in CRC-speci c death, and a 33% reduction in disease progression or survival 29 .…”
Section: Discussionmentioning
confidence: 99%
“…Evidence suggests that lactase persistent individuals typically consume more milk than their lactase-non-persistent counterparts [ 67 , 68 ]. Given the known impact of milk consumption on CRC risk [ 26 , 27 , 69 , 70 , 71 , 72 , 73 , 74 ], it is plausible that the protective effect of LPH on CRC risk is partially mediated through catalyzed products of milk [ 75 , 76 , 77 ] and key milk components, namely calcium [ 12 , 13 , 78 ] and vitamin D [ 14 , 79 ]. Other milk-derived compounds, such as butyric acid, conjugated linoleic acid, sphingolipids, and lactoferrin [ 80 , 81 , 82 ], also contribute to the protective effect of LPH.…”
Section: Discussionmentioning
confidence: 99%
“…There is also evidence linking calcium to a lower risk of mutations in the KRAS gene, a significant determinant in the carcinogenesis of CRC [ 6 ]. Vitamin D modulates molecular pathways relevant to CRC development, including the downregulation of the COX-2 gene and the upregulation of 15-hydroxyprostaglandin dehydrogenase (15-PDGH), leading to a reduction in local prostaglandin levels and hence inhibiting cancer cell survival [ 14 ]. Moreover, it interferes with β-catenin-mediated gene transcription, primarily by promoting Vitamin D receptor (VDR) binding to β-catenin, emphasizing its suppressive role on tumor growth [ 79 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the evidence on whether vitamin D intake or serum levels affect cancer incidence, progression, or mortality is mixed in observational studies and clinical trials. A large number of studies reported that higher intake or circulating vitamin D was associated with a decreased CRC risk ( 12 14 ). Conversely, these are null findings from randomized trials and systematic reviews ( 15 – 18 ).…”
Section: Introductionmentioning
confidence: 99%